2018
DOI: 10.1186/s12888-018-1973-7
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in depression prevalence and health-related correlates: results from population-based surveys in Germany 1997–1999 vs. 2009–2012

Abstract: BackgroundAlthough an “epidemic” of depression is frequently claimed, empirical evidence is inconsistent, depending on country, study design and depression assessment. Little is known about changes in depression over time in Germany, although health insurance companies report frequency increases. Here we examined time trends in depression prevalence, severity and health-related correlates in the general population.MethodsData were obtained from the mental health module of the “German Health Interview and Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 64 publications
(94 reference statements)
4
49
2
8
Order By: Relevance
“…Während sich das Hilfesuchverhalten entwickelt, bleibt jedoch die Häufigkeit von Depressionen bei einer standardisierten Erfassung in der Bevölkerung in demselben Zeitraum in Deutschland [5] sowie international [8] stabil. Daher ist ein Zuwachs an Morbidität, der den steilen Anstieg ärztlicher Depressionsdiagnosen in den GKV-Daten allein erklären könnte, unwahrscheinlich.…”
Section: Kein Zuwachs An Morbidität In Der Gesamtbevölkerungunclassified
See 1 more Smart Citation
“…Während sich das Hilfesuchverhalten entwickelt, bleibt jedoch die Häufigkeit von Depressionen bei einer standardisierten Erfassung in der Bevölkerung in demselben Zeitraum in Deutschland [5] sowie international [8] stabil. Daher ist ein Zuwachs an Morbidität, der den steilen Anstieg ärztlicher Depressionsdiagnosen in den GKV-Daten allein erklären könnte, unwahrscheinlich.…”
Section: Kein Zuwachs An Morbidität In Der Gesamtbevölkerungunclassified
“…Diese Entwicklung korrespondiert jedoch nicht mit einem entsprechenden Anstieg von Depressionsdiagnosen, wenn diese standardisiert und unabhängig von der Inanspruchnahme des Versorgungssystems in der Bevölkerung erfasst werden [5]. Vergleichbare Befunde werden auch international berichtet [6 -9] und u. a. als Veränderungen im Inanspruchnahmeverhalten von Menschen mit psychischen Störungen sowie Diagnoseund Codierverhalten der Behandelnden bei zeitlich stabiler Morbidität interpretiert.…”
unclassified
“…Another interesting issue is the lower mean age of the sample in this study compared with those of other studies, which may affect the level of suicidal behavior, and the results of this study also show that an age of 20 years or lower is associated with a higher level of suicide risk. Nowadays, depressive disorders can be found in the younger age groups, which is often associated with genetic factors and a family history of depression [29], can cause more severe symptoms [30], and may lead to higher rates of suicidality. A previous study found that pre-adult onset MDD patients (age lower than 18 years) were associated with a history of suicide attempts and current suicidal thoughts [31].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies find that the prevalence of mood and anxiety disorders have remained constant over time (Bretschneider et al, ; Patten et al, ). From 1990 to 2010, for instance, the global prevalence of major depressive disorder (MDD) remained around 4.4% and for anxiety disorders was 4% (Baxter et al, ).…”
Section: Mental Disorders and The Global Burden Of Diseasementioning
confidence: 99%